Molecular Organization of the 25S–18S rDNA IGS of Fagus sylvatica and Quercus suber: A Comparative Analysis - Inácio, Vera (Public Library of Science, 2014)
The 35S ribosomal DNA (rDNA) units, repeated in tandem at one or more chromosomal loci, are separated by an intergenic spacer (IGS) containing functional elements involved in the regulation of transcription of downstream rRNA genes. In the present work, we have compared the IGS molecular organizations in two divergent species of Fagaceae, Fagus sylvatica and Quercus suber, aiming to comprehend the evolution of the IGS sequences within the family. Self- and cross-hybridization FISH was done on representative species of the Fagaceae. The IGS length variability and the methylation level of 18 and 25S rRNA genes were assessed in representatives of three genera of this family: Fagus, Quercus and Castanea. The intergenic spacers in Beech and Cork Oak showed similar overall organizations comprising putative functional elements needed for rRNA gene activity and containing a non-transcribed spacer (NTS), a promoter region, and a 5′-external transcribed spacer. In the NTS: the sub-repeats structure in Beech is more organized than in Cork Oak, sharing some short motifs which results in the lowest sequence similarity of the entire IGS; the AT-rich region differed in both spacers by a GC-rich block inserted in Cork Oak. The 5′-ETS is the region with the higher similarity, having nonetheless different lengths. FISH with the NTS-5′-ETS revealed fainter signals in cross-hybridization in agreement with the divergence between genera. The diversity of IGS lengths revealed variants from ∼2 kb in Fagus, and Quercus up to 5.3 kb in Castanea, and a lack of correlation between the number of variants and the number of rDNA loci in several species. Methylation of 25S Bam HI site was confirmed in all species and detected for the first time in the 18S of Q. suber and Q. faginea. These results provide important clues for the evolutionary trends of the rDNA 25S-18S IGS in the Fagaceae family.